Agenesis of maxillary lateral incisor in an Angle Class II, Division 1 malocclusion patient - Thiesen,Guilherme (2015)
The present case report describes the orthodontic treatment of a patient with agenesis of maxillary left lateral incisor and Angle Class II, Division 1 malocclusion. The patient also presented with maxillary midline deviation and inclination of the occlusal plane in the anterior region. Treatment objectives were: correction of sagittal relationship between the maxilla and the mandible; correction of midline deviation, so as to cause maxillary and mandibular midlines to coincide; correction of overbite and leveling of the occlusal plane, so as to create ideal conditions for esthetic rehabilitation of anterior teeth. This case was presented to the Brazilian Board of Orthodontics and Dentofacial Orthopedics (BBO) as a requirement for the title of certified by the BBO.